2013
DOI: 10.3389/fpsyg.2013.00681
|View full text |Cite
|
Sign up to set email alerts
|

Windows to the soul: vision science as a tool for studying biological mechanisms of information processing deficits in schizophrenia

Abstract: Cognitive and information processing deficits are core features and important sources of disability in schizophrenia. Our understanding of the neural substrates of these deficits remains incomplete, in large part because the complexity of impairments in schizophrenia makes the identification of specific deficits very challenging. Vision science presents unique opportunities in this regard: many years of basic research have led to detailed characterization of relationships between structure and function in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 173 publications
(231 reference statements)
3
54
0
Order By: Relevance
“…Our results align with a growing literature showing impaired visual context processing in SZ (Butler et al , 2008, Notredame et al , 2014, Phillips and Silverstein, 2013, Yoon et al , 2013). Some of these deficits may be specific to peripheral vision, such as abnormal temporal processing (Chen et al , 2014) and spatial crowding (Kraehenmann et al , 2012, but see Robol et al , 2013).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results align with a growing literature showing impaired visual context processing in SZ (Butler et al , 2008, Notredame et al , 2014, Phillips and Silverstein, 2013, Yoon et al , 2013). Some of these deficits may be specific to peripheral vision, such as abnormal temporal processing (Chen et al , 2014) and spatial crowding (Kraehenmann et al , 2012, but see Robol et al , 2013).…”
Section: Discussionsupporting
confidence: 92%
“…It has been suggested that studying these impairments may provide insight into the neural underpinnings of this disorder; by precisely characterizing visual deficits in SZ, one may be able to attribute them to specific neural mechanisms (Butler et al , 2008, Notredame et al , 2014, Phillips and Silverstein, 2013, Yoon et al , 2013). A number of recent studies have shown weaker surround suppression among SZ patients compared with healthy controls (HC; Dakin et al , 2005, Robol et al , 2013, Schallmo et al , 2013, Seymour et al , 2013, Tadin et al , 2006, Tibber et al , 2013, Yang et al , 2013a, b, Yoon et al , 2009), but see (Barch et al , 2012, Chen et al , 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to these findings is evidence that suppression of motion information in schizophrenia may in some cases be increased compared to healthy controls (Chen, Norton and Ongur, 2008). Overall, however, there is ample evidence that surround suppression is often impaired in schizophrenia (Yoon et al, 2013).…”
Section: Surround Suppression and Divisive Normalizationmentioning
confidence: 83%
“…It is also called feature subset selection. Mosaic based images [25] which are merged into a particular hyperspectral image, is used for the data analysis and classification algorithms.…”
Section: Discussionmentioning
confidence: 99%